2019
DOI: 10.1039/c9rp00109c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring prospective chemistry teachers’ perceptions of precipitation, conception of precipitation reactions and visualization of the sub-microscopic level of precipitation reactions

Abstract: In this study, how prospective chemistry teachers (PCTs) perceive precipitation and conceptualize precipitation reactions at the symbolic level was explored. Further, it was of interest to identify PCTs’ visualization of the sub-microscopic level of precipitation reactions. The sample was drawn from the Chemistry Education Department at the Education Faculty of a Turkish Public University. A total of 46 PCTs (10 in the 4th semester, 15 in the 6th semester, and 21 in the 8th semester) participated in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Numerosas investigaciones han señalado la existencia de dificultades en la comprensión de los equilibrios de solubilidad, aunque se han centrado fundamentalmente en el estudio de problemas numéricos relacionados con el producto de solubilidad (Setiowati et al, 2018;Nakiboğlu y Nakiboğlu, 2019;Muchson et al, 2020).…”
Section: Dificultades En La Comprensión De Los Equilibrios De Solubil...unclassified
“…Numerosas investigaciones han señalado la existencia de dificultades en la comprensión de los equilibrios de solubilidad, aunque se han centrado fundamentalmente en el estudio de problemas numéricos relacionados con el producto de solubilidad (Setiowati et al, 2018;Nakiboğlu y Nakiboğlu, 2019;Muchson et al, 2020).…”
Section: Dificultades En La Comprensión De Los Equilibrios De Solubil...unclassified
“…Science education is the teaching and learning of science subjects including chemistry in schools, colleges and universities. Unfortunately, literature has proven that students at all levels have difficulty understanding chemistry for different reasons, but majorly for its abstract nature (Lu & Bi, 2016;Nakiboglu & Nakiboglu, 2019). It has been observed in the literature that studying chemistry is a stressful endeavor for many students causing poor academic achievement (Orimogunje, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that all level students have problems understanding chemistry topics and concepts (Nakhleh, 1992;Nakiboğlu, 2003;Nakiboğlu, 2006;Nakiboğlu and Nakiboğlu, 2019;Nyachwaya et al, 2011;Rahayu, Treagust and Chandrasegaran, 2021;Sanger and Greenbowe, 1997;Taber, 1994;Taber et all., 2012). The students can also have misconceptions about many chemistry concepts because chemistry concepts seem too abstract for students at this level.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons related to the problematic nature of chemistry learning is that understanding chemistry needs declarative, procedural, and relational knowledge and problemsolving skills which can each of containing low or high levels of cognitive complexity. This requires that students construct the relationships between facts, concepts, and or ideas within a learning task (Nakiboğlu and Nakiboğlu, 2019;2021). Because of all these, the chemistry course is one of the most challenging courses in upper-secondary schools and teachers can benefit from many support materials to teach chemistry topics and concepts in their lessons (Nakiboğlu, 2018).…”
Section: Introductionmentioning
confidence: 99%